The Art Of Social Work Practices In Indonesia The Impact of LSSR Policy on the Socio-Economic Sector in Banten Province - Muhammad Amin; Palupi Lindasari Samputra (Jurnal Ilmu Sosial Mamangan, 2021)
The Covid-19 pandemic is attacking the world, and measures are being taken to control the virus’s spread. Banten’s government is prohibited from enforcing the LSSR policy, which is based on Governor of Banten Decree 443 / Kep. 140-Huk / 2020 on the Establishment of Large-Scale Social Boundaries. This research employed quantitative descriptive method to determine if the LSSR impacts reducing the spread of the Covid-19 virus, as well as on the community’s social and economic well-being. The results indicated that unemployment would rise to 172 thousand by 2020. The poverty rate increased by 134.57 thousand. Income per capita decreases to 11,994 from 12,267 in 2019. The Human Development Index, which experienced a slowdown in growth in 2020, increased 0.01 points from 0.49 points the previous year. With an improvement of 0.15 points in the total length of schooling, it is greater than the 0.12point increase in 2019. The study recommends that the LSSR policy be maintained in order to prevent the spread of the Covid-19 virus, and that the government undertake fiscal stimulus efforts to improve the sustainability of micro, small, and medium-sized enterprises.